2012
DOI: 10.4269/ajtmh.2012.11-0312
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute Bacterial Meningitis in Children from a Malaria-Endemic Area of Papua New Guinea

Abstract: Abstract. Predictors of acute bacterial meningitis (ABM) were assessed in 554 children in Papua New Guinea 0.2-10 years of age who were hospitalized with culture-proven meningitis, probable meningitis, or non-meningitic illness investigated by lumbar puncture. Forty-seven (8.5%) had proven meningitis and 36 (6.5%) had probable meningitis. Neck stiffness, Kernig's and Brudzinski's signs and, in children < 18 months of age, a bulging fontanel had positive likelihood ratios (LRs) 4.3 for proven/probable ABM. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…All hospitalized children aged between 2 months and 10 years who presented with febrile seizures, impaired consciousness, coma or other clinical signs and symptoms suggestive of a possible CNS infection were screened for inclusion. A standardized case report form that included demographic and clinical data was completed [ 14 ], including details of the presenting illness, characteristics of seizures, vaccination history and past medical history. Trained research nurses and study clinicians carried out clinical assessment on admission.…”
Section: Methodsmentioning
confidence: 99%
“…All hospitalized children aged between 2 months and 10 years who presented with febrile seizures, impaired consciousness, coma or other clinical signs and symptoms suggestive of a possible CNS infection were screened for inclusion. A standardized case report form that included demographic and clinical data was completed [ 14 ], including details of the presenting illness, characteristics of seizures, vaccination history and past medical history. Trained research nurses and study clinicians carried out clinical assessment on admission.…”
Section: Methodsmentioning
confidence: 99%
“…[10] Data from India are limited to a retrospective study, where the prevalence of meningitis was 2.4% in children with first febrile seizures, 0.86% in simple febrile seizures, and 4.81% in complex febrile seizures. [3] In [12] According to AAP, febrile convulsions are associated with a temperature ≥100.4°C. In clinical practice, we have observed that children with meningitis usually have a high-grade fever.…”
Section: Discussionmentioning
confidence: 99%
“…The present analysis also shows that although the specificity of KCH-2002 signs excluding fever without malaria parasitaemia has not changed, sensitivity was again markedly reduced (to 58% from 86%). Malaria parasitaemia has been shown to augment predictive models for bacterial meningitis [11,29]; however, the significant morbidity and mortality associated with meningitis means a screening rule with higher sensitivity may be favourable despite lower specificity.…”
Section: Discussionmentioning
confidence: 99%